PELAKSANAAN FAUNGSI KELUARGA PADA PEREMPUAN BEKERJA (Studi Kasus Guru Sekolah Menengah Atas Di SMA N 1 Bangkinang dan SMA N 2 Bangkinang Kecamatan Bangkinang Kabupaten Kampar) - Yunita Sari; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The study authors did in High School District of the City Bangkinang Kampar regency namely SMA SMA N 1 and N 2 Bangkinang Bangkinang. This study, entitled "Implementation of Family Function In Women's Work (Case Study High School Teacher) In high school SMA N 1 and N 2 Bangkinang Bangkinang Bangkinang District of Kampar regency". Topics focus of this research is how the division of time high school teacher in carrying out the role of housewife. In this study, researchers used informants through key informant research where researchers have understood the initial information about the object of research as well as research informants using Snowball Sampling. Informants in this study are high school teachers Bangkinang City District of Kampar regency as many as 11 people. The author uses qualitative descriptive method and the data was analyzed qualitatively. Data instrument is observation, interview, Library Studies and documentation. From research by the author. The authors conclude that the characteristics of the respondents work, more are dependents in the top 3 people in because of the distance the child of the other nearby, which make the cost of education and the need for more and more in day-to-day, on average, respondents had high school upwards, and that makes respondents work due to economic factors that are difficult at this time. Respondents are very big role in the family income, the income distribution of respondents 40% to help meet the needs of the family. The remaining 60% is still the husbands who find the money to meet the family economy. 7 functions of the family, only 5 function which is still on the run and held on a regular basis and by others, that the function of affect, socialization, status determination, protection and economic functions. while two other functions, namely: lack of sexual and reproductive setting run, this is due to the busyness of the respondents outside the home so that sexual and reproductive function did not go well.Keywords: A housewife and her role. Substitute agents